Amoxicillin combined with textile microfibers remodels intestinal microbiota, epithelial integrity, and enteric neuronal homeostasis in Danio rerio - Tagliamento, Manuela Agulló. [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
The coexistence of pharmaceutical residues and microfibers in aquatic environments raises concerns about their combined effect on organisms within ecosystems. This study investigated how the mode of exposure to amoxicillin, either alone or previously adsorbed onto synthetic (polyester) or natural (cotton) fibers, influences intestinal homeostasis in fish. To this end, intestinal biomarkers such as microbial composition, epithelial morphology, tight junction (occludin) levels, oxidative stress parameters, and enteric pan-neuronal density were evaluated. Exposure to amoxicillin induced pronounced microbiota alteration, a decrease in goblet cells, thinning of the epithelium, suppression of antioxidant defenses, increased lipid peroxidation and DNA damage, and a notable reduction in enteric neuronal density. Isolated fibers mainly caused moderate structural and redox changes. In contrast, amoxicillin combined with fibers led to different response patterns depending on the fiber type. Amoxicillin associated with polyester promoted partial recovery of epithelial parameters and GPx activation, although tight junction disruption persisted. Amoxicillin associated with cotton induced marked oxidative stress, mucosal remodeling, increased villus dimensions, elevated occludin levels, and high histopathological scores, but without a proportional loss of neurons. Principal component analysis confirmed a clear separation among exposure scenarios, highlighting that the antibiotic's physicochemical properties reshaped the biological signature of intestinal toxicity. Altogether, our findings demonstrate that environmental fibers can modulate not only the magnitude but also the nature of antibiotic-induced intestinal responses. These results emphasize the importance of considering particle–contaminant interactions in ecotoxicological risk assessments, as combined exposures may produce complex, exposure-form-dependent outcomes in aquatic organisms.

A coexistência de resíduos farmacêuticos e microfibras em ambientes aquáticos desperta preocupação quanto aos seus efeitos combinados sobre os organismos dos ecossistemas. Este estudo investigou como a forma de exposição à amoxicilina, isoladamente ou previamente adsorvida em fibras sintéticas (poliéster) ou naturais (algodão), influencia a homeostase intestinal em peixes. Para isso, foram avaliados biomarcadores intestinais, incluindo a composição da microbiota, a morfologia do epitélio, os níveis da proteína de junção ocludina, parâmetros de estresse oxidativo e a densidade pan-neuronal do sistema nervoso entérico. A exposição à amoxicilina induziu alterações pronunciadas na microbiota, redução das células caliciformes, afinamento do epitélio, supressão das defesas antioxidantes, aumento da peroxidação lipídica e dos danos ao DNA, além de uma redução significativa da densidade neuronal entérica. As fibras isoladas promoveram principalmente alterações estruturais e redox moderadas. Em contraste, a amoxicilina combinada às fibras desencadeou diferentes padrões de resposta, dependendo do tipo de fibra. A amoxicilina associada ao poliéster promoveu recuperação parcial dos parâmetros epiteliais e ativação da glutationa peroxidase (GPx), embora a desorganização das junções celulares tenha persistido. Já a amoxicilina associada ao algodão induziu intenso estresse oxidativo, remodelamento da mucosa, aumento das dimensões das vilosidades, elevação dos níveis de ocludina e altos escores histopatológicos, porém sem uma perda proporcional de neurônios. A análise de componentes principais confirmou uma clara separação entre os diferentes cenários de exposição, evidenciando que as propriedades físico-químicas do antibiótico remodelaram a assinatura biológica da toxicidade intestinal. Em conjunto, nossos resultados demonstram que as fibras presentes no ambiente podem modular não apenas a magnitude, mas também a natureza das respostas intestinais induzidas por antibióticos. Esses achados reforçam a importância de considerar as interações entre partículas e contaminantes nas avaliações de risco ecotoxicológico, uma vez que exposições combinadas podem produzir respostas complexas e dependentes da forma de exposição em organismos aquáticos.
A amoxicilina associada à microfibras remodela a microbiota intestinal, a integridade epitelial e a homeostase neuronal entérica em peixes
Keywords: Polyester; Cotton; Antibiotic; Intestinal barrier; Oxidative stress; Antibacterianos; Algodão; Poliéster; Estresse oxidativo; Intestinos; Peixes